A MIOIR case study on public procurement and innovation: DWP work programme procurement - Delivering innovation for efficiencies or for claimants? - Su Maddock (The University of Manchester, Manchester Business School, 2012)
This paper is a study of the UK government's Welfare to Work Programme between 2011 and 2012 and provides a critique of the Department of Work and Pension's commissioning and procurement process.The study draws on the views of relevant stakeholders and to the impact of two-tier procurement, business model and to the 'payment by results' system on the personalised services provided for claimants and to government practice efficiencies at a time of austerity. In particular the study assesses how far the various types of innovation that DWP has adopted for the programme and draws attention to the significance of the wider commissioning framework and role of government in creating systems to support public service innovation. A recent House of Lords Report confirmed the importance of commissioning and procurement in capturing and embedding innovation; however, it also raised doubts about innovation procurement practice and the competence of procurers. Innovation policy is rarely underpinned by empirical research and the policy debate on 'procurement' is largely based on assumptions that public service innovation uptake can be managed and taken to scale by public institutions and existing systems. The Work Programme, managed by the Department of Work and Pensions (DWP) is therefore an obvious choice for research on public procurement and innovation. This study is part of the larger MIOIR Project on Public Procurement and Innovation entitled Underpinn which is funded by the ESRC/BIS/NESTA/TSB. It is based on detailed interviews with DWP senior officials and procurement teams, local government officers, procurement consultants, and directors and board members of specialist suppliers and prime contractors.
Keywords: 330; Öffentlicher Auftrag; Innovationsmanagement; Arbeitsmarktpolitik; Großbritannien